1999
DOI: 10.1098/rstb.1999.0380
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between proteins implicated in exocytosis and voltage–gated calcium channels

Abstract: Neurotransmitter release from synaptic vesicles is triggered by voltage-gated calcium in£ux through P/Q-type or N-type calcium channels. Puri¢cation of N-type channels from rat brain synaptosomes initially suggested molecular interactions between calcium channels and two key proteins implicated in exocytosis: synaptotagmin I and syntaxin 1. Co-immunoprecipitation experiments were consistent with the hypothesis that both N-and P/Q-type calcium channels, but not L-type channels, are associated with the 7S comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 53 publications
2
50
2
2
Order By: Relevance
“…For example, Syt III may sense an increase in intracellular Ca 2ϩ due to influx of extracellular Ca 2ϩ , whereas Syt VII may be relevant when intracellular Ca 2ϩ elevation is induced by intracellular mobilization through inositol 1,4,5-trisphosphate receptors. It has been demonstrated that synaptotagmin directly interacts with N-type (49 -57) or P/Q-type (19,54,55) Ca 2ϩ channels in neurons and Lc-type Ca 2ϩ channels (20). Inositol 1,4,5-trisphosphate receptors are present in pancreatic ␤-cells; however, it is currently unclear whether they associate with synaptotagmin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Syt III may sense an increase in intracellular Ca 2ϩ due to influx of extracellular Ca 2ϩ , whereas Syt VII may be relevant when intracellular Ca 2ϩ elevation is induced by intracellular mobilization through inositol 1,4,5-trisphosphate receptors. It has been demonstrated that synaptotagmin directly interacts with N-type (49 -57) or P/Q-type (19,54,55) Ca 2ϩ channels in neurons and Lc-type Ca 2ϩ channels (20). Inositol 1,4,5-trisphosphate receptors are present in pancreatic ␤-cells; however, it is currently unclear whether they associate with synaptotagmin.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) The chaperone hsp70 is well known to interact with cysteine string proteins as syntaxin, synaptotagmin and SNAP-25 [37]. Synaptotagmin functionally interacts with Ca v 2.3d containing E-/ R-type voltage-gated Ca 2+ channels recruiting the protein complex to the plasma membrane of Xenopus oocytes which only would be possible according to panel B [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction might serve as a molecular link between synaptic vesicles and the calcium channels and in addition might modulate channel function (Seagar et al, 1999). To investigate the functional consequences of Syt1 phosphorylation during exocytosis triggered by calcium influx, we applied a voltage protocol that allows us to distinguish a subpopulation of the RRP, which is located close to calcium channels [immediately releasable pool (IRP)] (Horrigan and Bookman, 1994; Voets et al, 1999).…”
Section: Mutation Of Syt1 At Phosphorylation Sites Leaves Secretion Umentioning
confidence: 99%